BRAINSTORMING, EXPLORING, SHARING, TRANSFERRING KNOWLEDGE (BEST) AS AN EFFECTIVE STRATEGY TO UPRAISE STUDENTS’ WRITING SKILLS - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
Writing ability is one of the abilities of a student to contribute what they know. Writing is a language skill that has an important role in human life. In writing students often encounter several obstacles, therefore, teachers are encouraged to implement appropriate teaching methods to ensure that the learning activities become effective. This study made use of a classroom action research design with two cycles of learning activities to improve students' writing skills through BEST strategy. Data were collected through pre-test, post-test, and questionnaire. The results showed that the writing skill of the students improved significantly from the first and second cycles when compared to the results of the pre-test. Therefore, the BEST strategy is considered very effective for teaching writing skills. This study implies that teachers should consider using BEST strategy to enhance students' writing skills.